Cover Feature: Molecular Encapsulation Inside Microtubules Based on Tau‐Derived Peptides (Chem. Eur. J. 56/2018). Issue 56 (24th September 2018) - Inaba, Hiroshi; Yamamoto, Takahisa; Kabir, Arif Md. Rashedul; Kakugo, Akira; Sada, Kazuki; Matsuura, Kazunori
Abstract : A methodology for molecular encapsulation inside hollow microtubules has been developed based on the peptide design. A peptide derived from Tau protein binds to a pocket of tubulin (component of microtubules), which is located at the inner surface of the microtubules. The Tau‐derived peptide can be used to encapsulate exogenous cargos inside microtubules. The cover image shows the peptide—gold nanoparticle conjugates bound to tubulin and subsequently introduced to the inside of the microtubules. More information can be found in the Full Paper by H. Inaba, K. Matsuura, et al. onpage 14958 .